2012
DOI: 10.1074/jbc.m111.293605
|View full text |Cite
|
Sign up to set email alerts
|

Acridine Yellow G Blocks Glioblastoma Growth via Dual Inhibition of Epidermal Growth Factor Receptor and Protein Kinase C Kinases

Abstract: Background: PTEN deletion renders glioblastomas resistant to epidermal growth factor receptor (EGFR) inhibitors. Results: Acridine yellow G inhibits both EGFR and PKCs, resulting in cell growth repression, cell cycle arrest in the G 1 phase, and shrinkage of brain tumors. Conclusion: Acridine yellow G is a potent anti-tumor agent for malignant gliomas. Significance: Combinatorial inhibition of EGFR and PKCs provides the proof of concept for treating glioblastomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The anti-apoptotic Bcl-2 protein helps to block apoptosis cascade by preventing the release of mitochondrial apoptogenic factors, presumably via interaction with the mitochondrial porin channel [25]. Bax, proapoptotic protein, is responsible for the release of mitochondrial intermembrane space proteins, such as cytochrome c, Smac/Diablo, EndoG, Omi/HtrA2 and AIF [11,16]. The ratio Bax/Bcl-2 have been demonstrated as an indicator of apoptosis and regulation of the ratio is one of the mechanisms involving apoptosis induction [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anti-apoptotic Bcl-2 protein helps to block apoptosis cascade by preventing the release of mitochondrial apoptogenic factors, presumably via interaction with the mitochondrial porin channel [25]. Bax, proapoptotic protein, is responsible for the release of mitochondrial intermembrane space proteins, such as cytochrome c, Smac/Diablo, EndoG, Omi/HtrA2 and AIF [11,16]. The ratio Bax/Bcl-2 have been demonstrated as an indicator of apoptosis and regulation of the ratio is one of the mechanisms involving apoptosis induction [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…After 24, 48, and 72 hours of incubation, the culture medium was removed and the cells washed twice with PBS. MTT assay was carried out as described with little modification [11]. Then 0.5 mg/ml MTT solution was added to each well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When tested in U87MG cell lines, acridine yellow G directly inhibits the kinases EGFR and PKCs with IC50 values of ∼7.5 and 5 μM, respectively, consequentially blocking the mTOR signaling and triggering the cell cycle arrest in the G 1 phase, and, in turn, activating the apoptotic process in tumors. In particular, acridine yellow G preferentially blocks cell proliferation of the most malignant U87MG/EGFRvIII cells (PTEN-deficient U87MG glioblastoma cells that overexpress EGFRvIII) over the less malignant PTEN stably transfected U87MG cells ( Qi et al, 2012 ). In vivo studies indicated that Acridine yellow G has the ability to induce a reduction of the tumor volumes in both subcutaneous and intracranial mice models.…”
Section: The Multi-targeted Strategymentioning
confidence: 99%
“…Toxic effects in animals subjected to chronic treatment were undetectable. Globally, results indicate that Acridine yellow G is a safe and effective therapeutic agent for the treatment of aggressive gliomas, as well as other types of human cancers, such as lung cancer, that are also inhibited by this compound ( Qi et al, 2012 ).…”
Section: The Multi-targeted Strategymentioning
confidence: 99%